Probiotics: Potential Novel Therapeutics Against Fungal Infections - Wu, Yunjian; Hu, Shan; Wu, Changyu; Gu, Feng; Yang, Ying (Frontiers in Cellular and Infection Microbiology, 2022)
The global infection rate of fungal diseases is increasing year by year, and it has gradually become one of the most serious infectious diseases threatening human health. However, the side effects of antifungal drugs and the fungal resistance to these drugs are gradually increasing. Therefore, the development of new broad-spectrum, safe, and economical alternatives to antibacterial drugs are essential. Probiotics are microorganisms that are beneficial for human health. They boost human immunity, resist pathogen colonization, and reduce pathogen infection. Many investigations have shown their inhibitory activity on a wide range of pathogenic fungi. However, their antibacterial mechanism is still a secret. This article reviews the progress of probiotics as a new method for the treatment of fungal diseases.